Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Komitmen Organisasi - Ariiq Hisyam Prasetya; Agus Frianto (Jurnal Ilmu Manajemen, 2025)
The study aims to find out the impact of transformational leadership and organizational culture on organizational commitment in PT. X. This study uses quantitative research that sourced primary data from a questionnaire that has been distributed to the population of PT. X. The technique used for sampling is saturated samples with a total of 72 employees. The data analysis method in this study uses SEM with the help of the SmartPLS 3.2.9 software. The results of research show that transformational leadership has no influence on organizational commitment and organizational culture has a significant positive influence on organizational commitment.